Founding and sustaining grassroots actions in superdiverse neighbourhoods facing socioeconomic challenges: narratives of emergent processes, actions and resources - Gabriella Elgenius; Jenny Phillimore (Frontiers in Political Science)
The study contributes new knowledge about civil society and non-profit action in superdiverse neighbourhoods that face socioeconomic challenges in England and Sweden. Locally based grassroot organisations are of special interest and demonstrate substantial voluntary altruism. Since little is known about the nature of civil society in these conditions, this paper addresses a gap in knowledge using material from interviews with founders and actors of grassroots action and micro-mapping in four neighbourhoods. The analysis draws upon perspectives within Social Sciences to shed light on the offerings of grassroots activity with a particular focus on emergence narratives. Three axes of interest frame the analysis: actors’ motivations, resources and ways of working. In short, actors base their work on lived experiences and a shared vision to mitigate inequalities not addressed by mainstream services. Actors employ a creative use of local resources to achieve shared goals, building on the diversity of local population in innovative ways and developing value-driven assets-based approaches alongside flexible ways of working.